Exposure to a mixture of non-persistent environmental chemicals and neonatal thyroid function in a cohort with improved exposure assessment. (March 2023) - Coiffier, Ophélie; Nakiwala, Dorothy; Rolland, Matthieu; Malatesta, Andres; Lyon-Caen, Sarah; Chovelon, Benoît; Faure, Patrice; Sophie Gauchez, Anne; Guergour, Dorra; Sakhi, Amrit K.; Sabaredzovic, Azemira; Thomsen, Cathrine; et al.
Abstract: Background: In vitro and toxicological studies have shown that non-persistent environmental chemicals can perturb thyroid hormone homeostasis. Epidemiological studies with improved exposure assessment (i.e., repeated urine samples) are needed to evaluate effects of these compounds, individually or as a mixture, in humans. We studied the associations between prenatal exposure to non-persistent environmental chemicals and neonatal thyroid hormones. Methods: The study population consisted of 442 mother–child pairs from the French SEPAGES mother–child cohort recruited between July 2014 and July 2017. For each participant, four parabens, five bisphenols, triclosan, triclocarban, benzophenone-3 as well as metabolites of phthalates and of di(isononyl)cyclohexane-1, 2-dicarboxylate were assessed in two pools of repeated urine samples (median: 21 spot urines per pool), collected in the 2nd and 3rd trimesters of pregnancy, respectively. Thyroid stimulating hormone (TSH) and total thyroxine (T4) levels were determined in newborns from a heel-prick blood spot. Maternal iodine and selenium were assessed in urine and serum, respectively. Adjusted linear regression (uni-pollutant model) and Bayesian Kernel Machine Regression (BKMR, mixture model) were applied to study overall and sex-stratified associations between chemicals and hormone concentrations. Results: Interaction with child sex was detected for several compounds. Triclosan, three parabens, and one phthalate metabolite (OH-MPHP) were negatively associated with T4 among girls in the uni-pollutant model. BKMR also suggested a negative association between the mixture and T4 in girls, whereas in boys the association was positive. The mixture was not linked to TSH levels, and for this hormone the uni-pollutant model revealed associations with only a few compounds. Conclusion: Our study, based on repeated urine samples to assess exposure, showed that prenatal exposure to some phenols and phthalates disturb thyroid hormone homeostasis at birth. Furthermore, both uni-pollutant and mixture models, suggested effect modification by child sex, while, to date underlying mechanisms for such sex-differences are not well understood.